Features of Accounting Software Packages Affecting the Work Efficiency of Accounting Staff in Companies Located in Rojana Industrial Park, Phra Nakhon Si Ayutthaya Province - Phanchampee, Chanthawaree; Chutamas, Panyawat (MBA-KKU Journal, 2026)
The purposes of this research are to 1) examine the work efficiency of accounting staff based on the characteristics of accounting departments within organizations, and 2) investigate the features of accounting software packages affecting the work efficiency of accounting staff in companies located in Rojana Industrial Park, Phra Nakhon Si Ayutthaya Province. This study adopted a quantitative research design. The sample consisted of representatives of accounting staff from 153 companies located in Rojana Industrial Park. Data were collected using a questionnaire with a reliability coefficient of 0.96. The data were analyzed using frequency, percentage, mean, standard deviation, one-way analysis of variance (One-way ANOVA), and multiple regression analysis. The findings revealed that the work efficiency of accounting staff in companies located in Rojana Industrial Park differed significantly according to the characteristics of the accounting department, particularly the average work experience of accounting staff and their ability to use accounting software packages, at the .01 significance level. However, the number of accounting staff and the types of accounting software packages used did not result in significant differences in work efficiency. Regarding the features of accounting software packages, program capability, ease of use, data security, and compatibility with modern technology significantly influenced the overall work efficiency of accounting staff at the .05 and .01 significance levels, jointly explaining 49% of the variance in work efficiency (Adjusted R² = .49).